2013
DOI: 10.1002/pip.2429
|View full text |Cite
|
Sign up to set email alerts
|

A case study for micro-grid PV: lessons learned from a rural electrification project in India

Abstract: Micro-grids in developing countries present a significant application opportunity for photovoltaics (PV) as an energyenabling technology. The authors project 10 GW for this application in the next decade. The growth of this sector will be enhanced by shared learning of the best practices. The authors are part of a team that successfully installed 1/3 MW in micro-grids and presented the lessons learned and a useful methodology for determining key metrics. The PV is part of the rural electrification in India and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…For instance, in Afghanistan, nearly 50% of the beneficiaries of small-scale community-based renewable energy projects in selected areas reported that the projects helped them to improve their living conditions (Shoaib and Ariaratnam 2016). Loka et al (2014) found that decentralized micro-grid PV systems could benefit remote villages because they are both viable and cost effective. Proietti et al (2015) successfully tested the possibility of electricity generation from wind in high-altitude remote regions of Nepal.…”
Section: Ensuring Sustainable Energy Supplymentioning
confidence: 99%
“…For instance, in Afghanistan, nearly 50% of the beneficiaries of small-scale community-based renewable energy projects in selected areas reported that the projects helped them to improve their living conditions (Shoaib and Ariaratnam 2016). Loka et al (2014) found that decentralized micro-grid PV systems could benefit remote villages because they are both viable and cost effective. Proietti et al (2015) successfully tested the possibility of electricity generation from wind in high-altitude remote regions of Nepal.…”
Section: Ensuring Sustainable Energy Supplymentioning
confidence: 99%
“…8,9 In this paper, we focus on renewable DC sources of electricity and suggest an autonomous grid formulation to utilize the DC electric power, motivated by recent stand-alone solar power initiatives in rural areas in various developing countries. 6,10,11 We introduce a ring-coupled buck-type inverter system to utilize energy from DC power sources by converting it to AC voltage. The basic design of this grid is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In particular contexts, such as isolated and rural areas, or small islands, where energy supply from conventional sources (diesel, gas, etc.) is problematic and expensive and electrification by the public network is economically unjustified, the use of locally available resources such as biomasses [11], solar [12], and wind [13] can improve reliability, environmental impacts, and energy costs. Further efficiencies can be also reached integrating energy carriers such as electricity and thermal energy [14].…”
Section: Introductionmentioning
confidence: 99%